2019
DOI: 10.3390/v11040322
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Immunogenicity and Neutralisation Efficacy of Viral-Vectored Vaccines Against Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) has caused extensive outbreaks in several countries within the Americas, Asia, Oceanic/Pacific Islands, and Europe. In humans, CHIKV infections cause a debilitating disease with acute febrile illness and long-term polyarthralgia. Acute and chronic symptoms impose a major economic burden to health systems and contribute to poverty in affected countries. An efficacious vaccine would be an important step towards decreasing the disease burden caused by CHIKV infection. Despite no licensed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 53 publications
0
54
0
2
Order By: Relevance
“…Given that the ChAdOx1 CHIK vaccines described here are safe and effective, further characterization, including dosing and long-term immunogenicity studies in C57Bl/6 mice is warranted. The ChAdOx1 vectored vaccines described here were designed to express a multi-lineage mosaic protein with the aim to widen protection against all CHIKV lineages [14]. We hypothesized that as neutralizing antibodies against the CHIKV surface antigens correlate with protection, the capsid being the most internal structural protein might be less of a requirement to induce effective immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the ChAdOx1 CHIK vaccines described here are safe and effective, further characterization, including dosing and long-term immunogenicity studies in C57Bl/6 mice is warranted. The ChAdOx1 vectored vaccines described here were designed to express a multi-lineage mosaic protein with the aim to widen protection against all CHIKV lineages [14]. We hypothesized that as neutralizing antibodies against the CHIKV surface antigens correlate with protection, the capsid being the most internal structural protein might be less of a requirement to induce effective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenes were cloned into a pMono plasmid, under the control of a CMV promoter. More details have been described before [14]. ChAdOx1 Zika (Zika prME ∆TM) was used as a negative control [13].…”
Section: Cells Viruses and Vaccines Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the induction of anti-adenovirus immune response, human adenoviral-vectored vaccines are not suitable for humans. Chimpanzee adenovirus overcomes this problem to maintain vaccine efficacy (Lopez-Camacho et al, 2019). In this study, the full length or capsid-deleted structural proteins of CHIKV were expressed at the adenoviral platform to generated vaccines ChAdOx1 sCHIKV and ChAdOx1 sCHIKV C. A single dose of the two kinds of ChAdOx1 vaccines was injected in BALB/c mice.…”
Section: Recombinant Virus-vectored Vaccinementioning
confidence: 99%
“…ChAdOx1 has deletions on the E1 and E3 genes that render it replication-deficient thereby enhancing its safety ( 32 ). We have previously reported that ChAdOx1 encoding CHIKV structural proteins (ChAdOx1 Chik) elicits long-lasting IgG antibodies against CHIKV E2 in BALB/c mice ( 33 ). ELISA measurements at two weeks, six weeks and 10 months post vaccination, showed that the levels of IgG anti-CHIKV E2 are maintained over time, suggesting long term immunity of at least 10 months.…”
Section: Introductionmentioning
confidence: 99%